An Cháilíocht sa Ghaeilge: What are Your Options? - Whelton, Marie; Mac Giolla Bhríghde, Peadar (Irish National Teachers' Organisation, 2023)
This article aims to provide candidates of An Cháilíocht sa Ghaeilge (SCG/OCG) with information and guidance on the application process, routes to completion, important dates (2023-2024) and available supports.
Keywords: An Cháilíocht sa Ghaeilge (SCG/OCG); Irish Language Requirement Examination; Gaeilge; Support Materials and Guidance for SCG/OCG; Differences between SCG and OCG; SCG/OCG 2023-2024; Education--Ireland; Irish language--Study and teaching